Extending the Discussion: An Editor's Addition to the Topics Addressed in "A Content Analysis of Update: Applications of Research in Music Education (1989–2017)". (October 2019) - Rohwer, Debbie
Silvey, Sims, Pohlman, and Regier's content analysis in the current issue of Update documented the methodologies, topics, and populations used in Update studies from 1989 to 2017. To extend the discussion, I am going to add context from an editor's perspective on article format/context, coauthor/repeat authorship, and time that articles spent with authors and reviewers during the time period when Update had online submissions accepted through Sage.